Longitudinal Changes in MRI Muscle Morphometry and Composition in People With Inclusion Body Myositis. (30th August 2022) - Laurent, Didier; Riek, Jon; Sinclair, Christopher D.J.; Houston, Parul; Roubenoff, Ronenn; Papanicolaou, Dimitris A.; Nagy, Attila; Pieper, Steve; Yousry, Tarek A.; Hanna, Michael G.; Thornton, John S.; Machado, Pedro M.
Abstract : Background and Objectives: Limited data suggest that quantitative MRI (qMRI) measures have potential to be used as trial outcome measures in sporadic inclusion body myositis (sIBM) and as a noninvasive assessment tool to study sIBM muscle pathologic processes. Our aim was to evaluate changes in muscle structure and composition using a comprehensive multiparameter set of qMRI measures and to assess construct validity and responsiveness of qMRI measures in people with sIBM. Methods: This was a prospective observational cohort study with assessments at baseline (n = 30) and 1 year (n = 26). qMRI assessments include thigh muscle volume (TMV), inter/intramuscular adipose tissue (IMAT), muscle fat fraction (FF), muscle inflammation (T2 relaxation time), IMAT from T2* relaxation (T2*-IMAT), intermuscular connective tissue from T2* relaxation (T2*-IMCT), and muscle macromolecular structure from the magnetization transfer ratio (MTR). Physical performance assessments include sIBM Physical Functioning Assessment (sIFA), 6-minute walk distance, and quantitative muscle testing of the quadriceps. Correlations were assessed using the Spearman correlation coefficient. Responsiveness was assessed using the standardized response mean (SRM). Results: After 1 year, we observed a reduction in TMV (6.8%, p < 0.001) and muscle T2 (6.7%, p = 0.035), an increase in IMAT (9.7%, p < 0.001), FF (11.2%, p = 0.030), connective tissue (22%, p = 0.995), and T2 *-IMAT (24%, p < 0.001), and alteration in muscle macromolecular structure (ΔMTR = −26%, p = 0.002). A decrease in muscle T2 correlated with an increase in T2*-IMAT ( r = −0.47, p = 0.008). Deposition of connective tissue and IMAT correlated with deterioration in sIFA ( r = 0.38, p = 0.032; r = 0.34, p = 0.048; respectively), whereas a decrease in TMV correlated with a decrease in quantitative muscle testing ( r = 0.36, p = 0.035). The most responsive qMRI measures were T2*-IMAT (SRM = 1.50), TMV (SRM = −1.23), IMAT (SRM = 1.20), MTR (SRM = −0.83), and T2 relaxation time (SRM = −0.65). Discussion: Progressive deterioration in muscle quality measured by qMRI is associated with a decline in physical performance. Inflammation may play a role in triggering fat infiltration into muscle. qMRI provides valid and responsive measures that might prove valuable in sIBM experimental trials and assessment of muscle pathologic processes. Classification of Evidence: This study provides Class I evidence that qMRI outcome measures are associated with physical performance measures in patients with sIBM.